A Modern Greek online course designed through participatory design and social distributed constructionism - Zaphiris, Panayiotis; Laghos, Andrew; Zacharia, Giorgos (My University, 2003)
We will be presenting the implementation of Distributed Constructionism (DC) through a Participatory Design (PD) methodology for an Online Learning community. As an extension to a previous project, we will be setting up a face-to-face physical team with Greeks and Cypriots of Diaspora who would collaborate on the content and functionality development of an online Modern Greek language course, peer review and publish content contributions, through their involvement in participatory design teams. Participatory design will be implemented as a four step process: (a) Build bridges with the intended users (b) Map user needs and suggestions to the system (c) Develop a prototype (d) Integrate feedback and continue the iteration.
Keywords: Computer Supported Collaborated Learning (CSCL); Distributed Constructionism (DC); Participatory Design (PD)